Review of Criminal Liability Law Disbursement of Fictive Credit Funds by Banks in Perspective of Criminal Aspects of Banking - Rizki Maulana, Tubagus Vibi; Gunarto, Gunarto (Jurnal Hukum Khaira Ummah, 2025)
The anatomical pattern of fictitious mode crimes can be used by banks, some elements of fictitious mode only, or all elements of fictitious mode are used, so that this fictitious mode can be faced by banks because it comes from outside or from within. But banks can also use it themselves from outside and from within, when the bank uses fictitious mode from outside and from within, then the funds that are actually distributed will appear and the funds that are distributed are only records or documents or transactions, but the funds do not exist or are empty, imaginary, so that they become fictitious, then fictitious funds or credit funds become fictitious credit. This research aims to find out and analyze (1) the legal nature of criminal policy in the banking sector, (2) patterns of criminal responsibility for the disbursement of fictitious credit funds by banks, (3) legal problems of criminal responsibility in cases of disbursement of fictitious credit funds by banks. The approach method used in this study is normative juridical. The specifications of this study are descriptive analytical. The data source used is secondary data. Secondary data is data obtained from library research consisting of primary legal materials, secondary legal materials and tertiary legal materials. The results of the study and discussion can be concluded: (1) Law No. 10 of 1998 concerning Banking, specifies thirteen types of banking crimes (Articles 46 to 50), of which thirteen crimes can be classified into four types of crimes, namely: crimes related to licensing; crimes related to bank secrecy; crimes related to supervision and guidance; crimes related to banking business. (2) Implicated by the provisions of laws and regulations governing fictitious credit, the suspect can be subject to criminal responsibility under Article 49 of Law No. 10 of 1998 concerning Amendments to Law No. 7 of 1992 concerning Banking. Paragraph 1 states that: Members of the Board of Commissioners, Directors or bank employees who intentionally make or cause false records to be made in the books or in the reporting process, or in documents or reports on business activities, transaction reports or accounts of a bank. (3) Conceptually, the cumulative-alternative formulation system has been regulated in Law Number 1 of 2023 concerning the Criminal Code, whereby if the fine is not paid, the property is confiscated and auctioned to pay the fine or taken from the convict's income and if there is none (not enough), a substitute prison sentence/imprisonment is imposed for a period not exceeding the maximum prison sentence/imprisonment threatened.